Sentence skeleton and signpost words to develop english writing skills among students of eighth-year “a”, afternoon session at 27 de febrero high school in the city of loja during 2019-2020 school year - Palacio Armijos, Larry Bryan (2020)
This research work was addressed to improve the English writing skills through sentence skeleton and signpost words techniques among students of eighth-year “A”, afternoon session at 27 de Febrero High School during the 2019-2020 school year. The scientific, descriptive, analytic-synthetic and statistical method assisted to compile theoretical information, describe the stages of the research, analyze, process and interpret the data gathered. Tests and questionnaires were applied to thirty-two students to diagnose and assess their progress on writing skills, and attitudes towards the applied techniques. The observation sheets and reflective journals were beneficial to register students’ development of writing skills as well as their attitude towards the techniques. The results showed a significant improvement in students’ writing skills, specifically in word order, punctuation and tense. To conclude, the application of sentence skeleton and signpost words techniques assisted students to improve significantly their writing skills. It also enabled them to work collaboratively with their classmates.